The effect of literacy-based rhythmic gymnastics on motor skills and comprehension in first graders - Bustanol Arifin; Laura Salsabilla; Heru Wardana Yoga; Beti Istanti Suwandayani (Research and Development in Education (RaDEn), 2025)
This study explores the impact of literacy-based rhythmic gymnastics on motor skills and comprehension among first-grade students at Muhammadiyah Elementary School 8, Malang, East Java. Using a qualitative observational approach, the research highlights how this innovative learning method combines rhythmic movements with educational songs and stories, creating a holistic educational experience. Data were collected through direct observations, semi-structured interviews with teachers and parents, and documentation of student activities. Thematic analysis was conducted using NVivo 12 software to identify patterns related to student engagement, motor skill development, and literacy comprehension. The results reveal that rhythmic gymnastics significantly improves students' motor coordination, balance, and flexibility while enhancing their ability to follow instructions and connect movements to narratives or songs. Parents reported increased creativity as students expressed their understanding through drawing gymnastic movements. Literacy skills, such as reading, writing, and memorizing, were also positively influenced by integrating musical and storytelling elements into the activities. This study concludes that literacy-based rhythmic gymnastics is an effective, interactive, and enjoyable approach to fostering holistic child development. It recommends broader implementation in various educational settings and further exploration of its impact across different age groups and cultural contexts. This approach can potentially create meaningful and engaging learning experiences for young learners.